Metode Pelaksanaan Pekerjaan Pondasi Bore Pile Pada Proyek Penanganan Longsoran Ruas Jalan Bts. Kota Sumedang – Cijelag STA 19+198 Jawa Barat - Sembada, Abdi; Kholiq, Abdul (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
The implementation of bore pile foundations in the Cirebon Regency – Majalengka Regency – Sumedang Regency Road Preservation Project is one of the avalanche handling work items that aims to strengthen the soil retaining wall structure from the load of the structure on it, the soil retaining wall structure was built because the existing condition had previously collapsed so a new soil retaining wall was planned. The foundation used in the construction of this soil retaining wall is a bore pile foundation. Bore pile foundation is a type of deep foundation whose installation is carried out first by drilling the ground with the diameter of the drilling hole according to the plan using a hydraulic drilling machine until it reaches a predetermined depth, then an assembled steel frame is inserted, and casting is carried out using a concrete mixture. The purpose of this study is to find out the stages of bore pile foundation work in the Avalanche Handling Project from the preparation of tools and materials to the implementation of the work. Knowing how to drill and install bore pile reinforcement. Knowing how bore pile casting works. In the implementation of bore pile work in the Avalanche Handling project of the Sumedang City Boundary Road section of STA 19 + 198, there are several stages, namely preparatory work, drilling work, rebar installation work, and casting work.